Patent Ductus Arteriosus (P.D.A.) (An analysis of 37 surgically proved cases) - O. J. Rachman; A. Hanafiah; I. S. F. Ranti (Indonesian Pediatric Society, 1976)
An analysis of the clinical picture on 37 cases of patent ductus arteriosus proved by operation is presented, including the chest X-ray and electrocardiographic findings. In 13 cases preoperative hemodynamic studies were necessary to establish the diagnosis, although in most of the cases it could be based on clinical findings only. During the years 1968 to 1973, 37 patients were operated upon for patent ductus arteriosus (PDA) at the Cardiologic Center, Dr. Cipto Mangunkusumo Hospital, Medical School University of Indonesia, Jakarta. This paper is meant to analyze the clinical picture and in some instances, the hemodynamic findings of those 37 patients.